Representations of Female Masculinity Bandelnya Judith Series by Andi Bachtiar Yusuf: Roland Barthes Semiotic Studies - Galuh Indriyanti; Memet Sudaryanto; Nur Indah Sholikhati (Transpublika Publisher, 2025)
Studies on gender representation in contemporary Indonesian film and series increasingly highlight how female characters challenge traditional norms of femininity. However, depictions of women with masculine traits are still relatively limited, creating a gap in understanding how such identities are constructed through visual and verbal signs in local media. This research discusses the representation of female masculinity in the series Bandelnya Judith by Andi Bachtiar Yusuf using Barthes’ semiotic study. The aim of this research is to describe the form of female masculinity representation through visual and verbal signs found in the series. The research method used is descriptive qualitative with content analysis, while data was collected through non-participatory observation technique (SBLC), note-taking technique, and recording technique. The research results show that Judith’s character represents masculinity based on Chafetz’s criteria, namely physical appearance, functional, sexual, emotional, intellectual, interpersonal, and personal character. Through Barthes’ semiotic theory, it was found that denotative meaning displays masculine behavior directly, connotation affirms values or views toward visual imagery, while at the myth level there is a shift in social meaning showing social beliefs regarding women’s roles. The emerging myths show that masculine traits are not only possessed by men. This research found six out of seven Chafetz’s masculinity criteria demonstrated by Judith as the main character. This confirms that Judith represents a woman with masculine character who challenges traditional gender stereotypes and presents a new view that masculine traits are not only possessed by one particular gender.